ANALISIS FAKTOR-FAKTOR DIBALIK PRESTASI AKUNTABILITAS PEMERINTAH PROVINSI JAWA TIMUR - Astragina, Kalapie (Jurnal Akuntansi AKUNESA, 2013)
Indonesian government published regulation UU No. 15 on 2004 to respond the demand of the citizen about transparancy of financial governance to realizing the good governance concept. But, until now the precentage of provincial government?s financial report which can get Unqualified Opinion from BPK just 33%, it means that accountability of the provincial government?s financial still at the low rate. East Java Provincial Government has a good achievement for the audit opinion, the financial report can get Unqualified Opinion for the last three yaers since 2010. Considering this phenomena, the researcher would like to find out the factors behind East Java Provincial?s achievement. The results are the substitution of the governor, success rate of the main program which can make the economy rate of the East Java grow, harmonious coordination between the local government and BPK, participation of the citizen, the obedience with the regulation, and improvement of the information?s quality and technology. Keywords : Good governance, accountability, financial report, audit opinion.